Simulation of Water Allocation Optimization Problem - Agustriyanto, Rudy (Politeknik Elektronika Negeri Surabaya (PENS), 2018)
Pollution prevention is primarily stimulated by economics, legislation, liability concerns, and the enhanced environmental benefit of managing waste at source. Chemical process industries consume a huge amount of water. Consequently, wastewater streams from such industries which contain various contaminants may create environmental problem. The increasing cost of fresh water supply and wastewater treatment has encouraged process industries to minimize fresh water consumption and waste water generation. This paper presents a formulation of water allocation problem (WAP) in order to minimize fresh water consumption in multi contaminant mass exchanger network. The approach is based on mass balance equation within the system being studied. The problem were then solved by using Matlab Optimization Toolbox.